Aportación complementaria de las láminas proyectivas al psicodiagnóstico de Rorschach - Jiménez Gómez, Fernando (1989)
This paper makes reference to the Projective Inkblots developed by Rodríguez. These are intended to be complementary to the Roschach Inkblot Test. The author gives a description of the inkblots and their importance in diagnosis. Additional information concerning localization, determinants and content of the responses can be collected.